Analysis of Financial Performance Based on Financial Ratios at PT. Garuda Indonesia TBK Listed on the IDX in 2021-2023 - Dinda Arnelia Suryani; Heleun Auliasari; Erwin Budianto (International Journal Labs, 2025)
PT Garuda Indonesia Tbk, Indonesia’s national airline, has experienced prolonged financial distress caused by operational inefficiencies, debt mismanagement, and the significant impact of the COVID-19 pandemic. Despite its strategic role in national connectivity and global reputation, Garuda continues to struggle in maintaining liquidity, solvency, profitability, and asset efficiency. This study aims to assess the company’s financial performance during the 2021–2023 period using key financial ratios. A descriptive quantitative method was employed, analyzing secondary data from the company’s official financial statements. The assessment covered four key ratios: liquidity (quick ratio and operating cash flow ratio), solvency (debt-to-asset and cash flow-to-debt), profitability (return on assets and net profit margin), and activity (total and fixed asset turnover). Results indicate slight improvements in liquidity and solvency, but performance remains below standard benchmarks. Profitability was volatile, with a significant recovery in 2022 followed by a decline in 2023. Asset efficiency remained weak throughout the period. These findings reveal Garuda’s unstable financial condition and the urgency for strategic restructuring. The study highlights the need for improved asset utilization, sustainable cost management, and continued financial monitoring to support recovery. Future research may explore qualitative factors like management strategies and industry dynamics.